A comprehensive measure assessing different types of problematic use of the internet among Chinese adolescents: The Assessment of Criteria for Specific Internet-use Disorders (ACSID-11) - Saffari, Mohsen; Chen, Chao-Ying; Chen, I-Hua; Ruckwongpatr, Kamolthip; Griffiths, Mark D.; Potenza, Marc N.; Wang, Xue Lian; Huang, Yu-Ting; Chen, Jung-Sheng; Tsai, Ching-Chung; Lin, Chung-Ying (Comprehensive psychiatry, 2024)
Problematic use of the internet (PUI) is prevalent, particularly among adolescents and young adults. Given the limited measures to assess specific types of PUI, which encompasses a broad spectrum of activities such as online gaming, social media use, pornography use, shopping, gambling, and web-streaming, Muller et al. (2022) developed the Assessment of Criteria for Specific Internet-use Disorders (ACSID-11) to comprehensively assess different types of PUI (i.e., gaming, shopping, social media use, gambling, and pornography use). The present study aimed to validate the Chinese ACSID-11 among adolescents incorporating cross-cultural adaptations. Using forward-backward translation method, a culturally adapted version of the ACSID-11 was prepared. Then, a cross-sectional online survey was administered between September 8 and September 26, 2023. Adolescents, using a convenience sample (N = 11,492; mean age = 16.42 years [SD ± 0.91]; 59.1% male), were recruited from six schools to complete the translated ACSID-11, Internet Gaming Disorder Scale-Short Form (IGDS9-SF), Bergen Social Media Addiction Scale (BSMAS), and Smartphone Application Based Addiction Scale (SABAS) via an online platform. Pearson correlation coefficients assessed convergent/discriminant validity. Factor structure and measurement invariance were examined through confirmatory factor analysis (CFA) and multi-group CFA. Cronbach's alpha and McDonald's omega tested internal consistency. Associations between the ACSID-11 components and other scales supported convergent validity (i.e., ACSID-11 gaming scale with IGDS9-SF [0.37 ≤ r ≤ 0.41]; social networks use scale with BSMAS [0.24 ≤ r ≤ 0.31]) and discriminant validity (i.e., online gambling scale with BSMAS [0.16 ≤ r ≤ 0.19] and with SABAS [0.11 ≤ r ≤ 0.13]). A four-factor solution indicated good fit with comparative fit index (CFI) ranging from 0.982 to 0.958. The ACSID-11 was measurement invariant across sexes (∆CFI = -0.001 to 0.000) and different levels of related addictive behaviors (∆CFI = -0.001 to 0.000). Both Cronbach's alpha and McDonald's omega (0.63 to 0.97) were acceptable for both frequency and intensity of responses. The ACSID-11 is an appropriate scale to assess different kinds of PUI among Chinese adolescents and students. Psychometric assessment of the measure in other cultures and among clinical samples is recommended. •The Assessment of Criteria for Specific Internet-use Disorders (ACSID-11) was translated into Chinese.•The ACSID-11 was found to have a four-factor structure among a large sample of Chinese adolescents.•The ACSID-11 had good correlations with other measures assessing problematic use of the internet.•The ACSID-11 was found to be measurement invariant across sexes and addictive behaviors.•The findings showed that ACSID-11 can be used in a pediatric population.